Effect of ultrasonic agitation on mechanical and corrosion properties of gold electrodeposits - 403010 Rohaizat @ Ruhaizat Kassim (Sekudai : UTM, 1993)
This project is regarding a study on the effect of ultrasonic agitation on mechanical and corrosion properties of gold electrodeposits. the parameters involved are ph, temperature and ultrasonic power while the mechanical properties are concentrated on hardness, porosity, ductility and adhesion of gold cosatings. mild steel were plated with nickel for 10 minutes before platedwith gold for 1 minute with different combination of parameters. the specimens later were subjected to various types of test, they were visual inspection, tensile test, salt spray test, microstructure and topography study.relationship on the effect of parameters on ht quality of the deposits werestudied. in this study, it may be concluded that the using of ultrasonic agitation could be beneficial where it increases the coating corrision resistenace, adhesion, the appearance of coating and reduce the porosity of thegold coating. meanwhile, it was also observed the that the ultrasonically agitated system resulted in reducing the strength and ductility of gold coating.